Деякі проблемні питання пред’явлення особи для впізнання неповнолітньому потерпілому від злочинів насильницького характеру - Карпінська, Н; Ліщинська-Мартинюк, О; Karpinska, N; Lishchynska-Martyniuk, O (СНУ імені Лесі Українки, 2019)
У статті висвітлюються проблемні питання пред’явлення особи для впізнання неповнолітньому потерпілому від злочинів насильницького характеру за чинним КПК України. Окрему увагу приділено правовій регламентації понять «неповнолітній», «малолітній», «дитина». Розкрито зміст слідчої дії – пред’явлення для впізнання крізь призму психологічних особливостей неповнолітньої особи. Розкрито питання способу та місця проведення впізнання, обгрунтовано необхідність попереднього психологічного вивчення дитини та використання «зеленої кімнати» як ефективної спеціально організованої системи заходів, яка запобігає повторній травматизації психіки та цілком може використовуватися при проведенні пред’явлення особи для впізнання неповнолітньому потерпілому. The article highlights in terms of the current Criminal Code of Ukraine some hotly debated issues in the procedure of introducing a person for identification to a juvenile victim of violent offenses. Particular attention is paid to the legal definition of the concepts of «minor», «juvenile», «child». The content of presentation for the recognition is elucidated through the prism of the psychological characteristics of a juvenile. The article presents the analysis of the methods and place of presentation for identification, substantiates the necessity of the child's previous psychological examination and the use of the «green room» as an effective specially organized system of measures that might prevent repeated injury to the psyche and may well be used during the presentation of a person for the identification to a minor victim. It has been revealed that the CPC of Ukraine does not contain any special norms concerning the participation of a minor in conducting a presentation for identification, and therefore the minors participate in the procedure on the general grounds. The authors emphasize the need for legislative consolidation in the CPC of Ukraine of the differentiation between the procedural status of a minor and the juvenile participant in the criminal process. The success of the presentation for identification of a person to a minor victim of violent crime depends on the location and arrangement of the premises in which it will be conducted. The author stresses the obligatory preliminary psychological examination of the juveniles, which makes it possible to prepare them for cooperation with law enforcement bodies. The competence of the persons conducting the presentation for identification is a key requirement.
Debatable Issues in the Procedure of Presentation of a Person for Identification to a Juvenile Victim of Violent Offenses
Keywords: дитина; неповнолітні; пред’явлення особи для впізнання; вік; психологічні особливості; child; juvenile; presentation of person for identification; age; psychological peculiarities